INFEKSI Cytomegalo virus (CMV) PADA IBU HAMIL DAN MANIFESTASINYA DI RONGGA MULUT - Dewanti, I Dewa Ayu Ratna (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2010)
Immune status in pregnancy was very impotant, because the effect for life to fetus andmother. If immune in pregnancy hasânt been attended, it will attack infection. Infection diseases was found in pregnancy was Cytomegalo virus (CMV) infection. Aims. This literature reviews purposes to information of CMV infection in pregnancy and manifestation in oral mucosa. Discussion. Infection in fetus could happen when mother could be reactivation, reinfection, it was assimptomatic and it ungiven sequele if it has been compared primer infection. That was caused maternal Ig G anti-CMVcould throug placenta and protective. Clinical symptom had been known from inflammation reaction. Oral manifestation could be vesicle and ulcer. Conclusion. CMV infection in pregnancy wasdanger infection for fetus and mother. It caused status immunity in pregnancy have been kept for prevent so that havenât infection.